2021
DOI: 10.1101/2021.06.08.447491
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ROS/RNS balancing, aerobic fermentation regulation and cell cycle control – a complex early trait (‘CoV-MAC-TED’) for combating SARS-CoV-2-induced cell reprogramming

Abstract: In a perspective entitled From plant survival under severe stress to anti-viral human defense we raised and justified the hypothesis that transcript level profiles of justified target genes established from in vitro somatic embryogenesis (SE) induction in plants as a reference compared to virus-induced profiles can identify differential virus signatures that link to harmful reprogramming. A standard profile of selected genes named ReprogVirus was proposed for in vitro-scanning of early virus-induced reprogramm… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 150 publications
(126 reference statements)
2
11
0
Order By: Relevance
“…Ethanol has been shown to reduce ROS levels and led to high induction of alternative oxidase (AOX) and glutathione-S-transferase transcripts (Nguyen et al, 2017). Transcriptome analyses at 2,4-D -induced reprogramming indicated that the extent of aerobic fermentation is connected to cell proliferation and was regulated by interacting levels of sucrose and AOX (Costa et al, 2021;preprint). Transient up-regulation of genes related to alcoholic and lactic fermentation was shown to be associated with glycolysis and modified complex stress signaling patterns with enhanced superoxide dismutase and decreased transcript levels of nitric oxide -producing nitrate reductase.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Ethanol has been shown to reduce ROS levels and led to high induction of alternative oxidase (AOX) and glutathione-S-transferase transcripts (Nguyen et al, 2017). Transcriptome analyses at 2,4-D -induced reprogramming indicated that the extent of aerobic fermentation is connected to cell proliferation and was regulated by interacting levels of sucrose and AOX (Costa et al, 2021;preprint). Transient up-regulation of genes related to alcoholic and lactic fermentation was shown to be associated with glycolysis and modified complex stress signaling patterns with enhanced superoxide dismutase and decreased transcript levels of nitric oxide -producing nitrate reductase.…”
Section: Introductionmentioning
confidence: 99%
“…Considering generality of these observations, we proposed a reference transcriptome profile to identify virus traits that link to harmful reprogramming (Arnholdt-Schmitt et al, 2021 In Press). This approach helped identifying an early trait for combating SARS-CoV-2 that covers ROS/RNS balancing, aerobic fermentation regulation and cell cycle control (Costa et al, 2021;preprint).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations